A design project on the manufacture of basic magnesium carbonate - Jacinto, Carmen C.; Miranda, Ruben C.; Uy, Estella C. (Diliman, Quezon City College of Engineering, 1972)
Capacity: 37,920 tons/year -- Plant area: 51,000 sq.ft. -- Plantation area: 600,000 sq.ft. -- Fixed capital cost: 20,000,000 -- Operating cost at maximum production: 15,809,000 -- Annual sales at maximum production: 25,400,000 -- Return of investment: 47.7% -- No. of major manufacturing steps: 12 -- Pay-off time: 2.12 years -- Break-even point: 40.4% maximum production -- Shut-down point: 9.55% maximum production
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Magnesium carbonate